Analisis Strategi Belajar Kosakata Bahasa Jepang pada Siswa SMA - MUHAJIR RIZKI AFDHOL; Febi Ariani Saragih; Virginia Rooselyne Paskaliana (Jurnal Pendidikan Bahasa Jepang Undiksha, 2022)
This research aims to analyze the types of Japanese vocabulary learning strategies that are most often used by high school students. The analysis of the use of Japanese vocabulary learning strategies is studied using the theory of language learning strategies from Rebecca L. Oxford. The methods used in this research are qualitative and quantitative methods. Qualitative methods are used to describe and analyze Japanese vocabulary learning strategies for high school students. The quantitative method is used to present data on the frequency of types of Japanese vocabulary learning strategies for high school students. The data sources in this study are batch 2020 of 11th-grade students BSBU SMA Negeri 6 Malang, while the data is obtained from the results of questionnaires filled out by students. The results of the analysis show that the Affective strategy is the type of strategy most often used by students to learn Japanese vocabulary with a percentage of 69.1%. Then the Cognitive strategy is the second most frequently used strategy by students with a percentage of 66.7%. The third strategy most often used by students is the Social strategy with a percentage of 63.6%. Then the Memory strategy is the fourth strategy, and the Metacognitive strategy is the fifth. While the compensation strategy is the strategy that is rarely used by students in learning Japanese vocabulary with a percentage of 47%.